Standing up and Speaking Out? British Muslims' Collective Action against Islamist Extremism. Issue 4 (2nd October 2019) - Shanaah, Sadi; Lindekilde, Lasse
ABSTRACT: Under what circumstances are British Muslims more willing to participate in collective action against Islamist extremism? The study is based on a survey experiment fielded to 825 British Muslims, comparing the mobilization outcome following an appeal by the government, the Muslim Council of Britain or no appeal (control condition). We find that action appeals do affect mobilization and that the effect of action appeals on mobilization outcomes is moderated by the level of trust in the actor behind the appeal. British Muslims distinguished by their level of trust in the government and the Muslim Council of Britain react differently to action appeals from these actors. Our results are robust to the control of a range of factors previously shown to be important for mobilization to collective action and have important theoretical and practical implications for counter-extremism policy.